Characterization of former athletes with gonarthrotic of Santiago de Cuba province - Abad, Lisbey Naranjo; Vidal, Viviana Romero; Sabatés, Hilda Rosa Rabilero (International research journal of management, IT and social sciences, 2020)
Gonarthrosis is one of the main causes of pain and disability affecting a large number of the population of former athletes in the provincial Santiago de Cuba. Precisely this research aims to characterize the population of former athletes studied, some qualitative variables of interest, their predominance, and frequency, emphasizing age, sex, sport, and degree of osteoarthritis by the scale of Kellgren and Lawrence; that evaluates the degrees of osteoarthritis observed in x-rays. A percentage of statistical analysis was used for the interpretation of the data. As fundamental results, the group of age intervals of 41 to 50 years with 47% could be observed; the male sex dominated with equal 50% percentile for both age groups of 41 to 50 and 61-60 years; games with balls predominated with 71%; and grade II or mild osteoarthrosis in knees predominated with 71.5%.